PENGARUH MEDIA VISUAL DAN TUBIAN TERHADAP HASIL BELAJAR STUKTUR BAHASA JERMAN - Tia Meutiawati (Jurnal Kependidikan, 1999)
The purpose of this quasi-experiment was to determine the effects of teaching techniqucs bv using visualmediamd dnh and ewm behwioron students' achievemcnt in learning German smrctutes.This quasi-experinagnt fourth senuster 6 wih a criterion-group daign wssconducted in fue academic yearlgg2ltggj a SMII 6 Yogyakarta.The sample t,us divided into two groups consisting of 20students with high and low entry behaviors respective$. The group was taugltt by using viswl wdia and tu second hy drills.Suderus'entry behwior nas determined by scores they obtaircdlrom their achievement in German hnguage at the end of the third senuster.Their achievemmt in German structures in this experimennl design tws mcasured by a strrcture test. Thc test had a validit.vr of 0,7A5 mdrehability r = 0,924.Alur the experimeruu ttu 4 semcster a two-rtyty ana$sis af varianci and the iwk"v+est with a lcvel ofsignificant alpha : 0,05 were used to test the hypotheses. Thc result indicated that:(l) There was no dffirence befiyeentlwstudents' achia,ement nught by using viswl media ditb; (2) For sudents with a high lcvel erury belwvior, there was no differmce in achievemews betweenusing visual media and drilts; (3) Howarcr students with low mtr-v behavior achieved higher scores with vistul media tlwn drilb.Th,s,this research impties tha smden* with low ewry belwior the usevisual media can be helpful.